KSZTAŁTOWANIE SIĘ TRANSGRANICZNEGO SYSTEMU OCHRONY OFIAR WYPADKÓW DROGOWYCH - Maśniak, Dorota (Zeszyty Prawnicze, 2017)
Formation of Transboundary System of the Victims’ of Motor Vehicle Accidents Protection Summary The regulations applying to m otor liability insurance have a considerable significance in the European law. The system of „green cards” was introduced to facilitate the fulfilment of claims in accidents caused by a motorist in a M em ber State other than that in which the vehicle is registered. This system ensures the payment of compensation to victims of accidents caused by visiting vehicles through a private-sector network of Green Card Bureaux set up by the insurers and established in all the M em ber States. Nevertheless, a significant gap has still remained: the original aim was to eliminate border controls on insurance, however the „green card” system covered only victims who were injured in their home country. it did not apply to the fulfilment of claims when the accident took place outside the victim’s residing country (so-called ‘visiting victims’). This gap was filled by the Fourth M otor Directive, which, amongst other things, provides for an efficient mechanism for recovering a damage caused by such accidents. Such mechanism has two objectives: to ensure that „visiting victims” are quickly compensated, and to set up an efficient system o f compensation that keeps legal costs at a m inim um . it is now proposed to extend this settlement mechanism to all accidents, regardless o f the victim’s residence. The Commission adopted a Proposal for a Fifth Motor Insurance Directive to improve the protection of victims.